Pedagogika specjalna jako przedmiot zainteresowania współpracowników lwowskiej „Szkoły” (w II połowie XIX wieku) - Wałęga, Agnieszka (Biuletyn Historii Wychowania, 2020)
oldest pedagogical journal published in Galicia, Eastern Europe, in the last 30 years of the 19th century. To date, these problems have not been analysed in detail in literature on the subject. The journal, devoted in particular to teachers’ training colleges and folk schools, was recommended to teachers in the south of Poland (which at that time was a part of the Austro-Hungarian Empire) as an important means of self-education. It was emphasized that knowledge acquired in teachers’ training colleges had to be broadened and the candidates for teachers, as well as professional Galician educators, should do it on their own. This concerned, among other things, the knowledge of the idiosyncrasies of working with disabled pupils. An analysis of the annual volumes of the journal from 1868–1899 demonstrates that its editors and collaborators dealt with issues in the field of oligophrenopedagogy, education of the deaf and people with impaired hearing, education of the blind and social rehabilitation. Articles published in the journal familiarized the readers with the history and contemporary problems of special education. They also supplied valuable educational and methodological instructions for parents, guardians and teachers of disabled children.